Technology-Based Fiqh Learning Development Strategy to Improve Student Understanding at Madani Al-Aziziyah High School - Fahmi (Program Magister Administrasi Publik, 2025)
This Classroom Action Research (PTK) was carried out with the aim of increasing students' understanding of Fiqh material through technology-based learning strategies at SMA MADANI Al-Aziziyah. Fiqh learning, which is generally carried out by conventional lecture methods, often makes students passive, bored, and less able to relate the material to real life. This condition creates a gap between the purpose of learning Fiqh, which is to form an understanding and skills of Islamic law practice and the results obtained in the classroom. Therefore, teachers need to implement innovative learning strategies by utilizing digital technology that is more in line with the characteristics of digital native generation students. This study uses the PTK model with two cycles consisting of planning, action, observation, and reflection stages. The learning media used include multimedia-based interactive presentations, worship tutorial videos, and online quiz applications such as Kahoot and Quizizz. The subjects of the study were 32 students in grade XI. Data was collected through learning outcome tests, observation of student activities, and teacher-student interviews. The results of the study show that technology-based Fiqh learning strategies have a significant positive impact. In the first cycle, student activity began to increase even though involvement was still limited, with an average test score of 72 and a percentage of learning completeness of 68%. After the improvement of the strategy in cycle II, student involvement increased significantly, students were more enthusiastic in participating in learning, and were able to work together in digital-based group discussions. The average test score increased to 82 with learning completeness reaching 88%. Thus, technology-based Fiqh learning has been proven to be effective in improving student understanding. The implications of this study show the importance of teacher training in mastering educational technology and the provision of supporting facilities from schools.